The Muhammadiyah’s Promotion of Moderation - Zakiyuddin Baidhawy (International Institute of Islamic Thought, 2015)
This article examines the role of the Muhammadiyah as the largest civil Islam movement in Indonesia in promoting moderation in the Muslim community. This study focuses on the Muhammadiyah’s efforts to establish its social ideals within the framework of civil society and the ummah. The findings of this study state that the social ideals of the Muhammadiyah to establish “Masyarakat Islam yang Sebenar-benarnya” (the Truly Islamic Society [MIYS]) have been implemented by playing its role in three domains. First, in the political domain the movement has utilized the public sphere and public opinion to democratize the state through collective deliberation and checks and balances on the state and public institutions, enforcing moderation and civility in diversity, and influencing the direction of state policy. Second, in the economic domain, the Muhammadiyah has attempted to build self-reliance, justice, and economic welfare through the development of religious-social philanthropy; to represent itself as the articulator and advocator of the interests of the marginalized people; and to build a healthy business for the social welfare. Third, in the cultural domain, it portrays itself as an intellectual and moral strength to enlighten the nation’s reason and conscience, to build consensus with the pillars of the state, as well as to enforce contestation and alternatives to the state.